Notes on Early Land Plants Today. 69. Circumscription of Plagiochilaceae (Marchantiophyta) with a preliminary infrageneric subdivision of Plagiochila - Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2015)
Plagiochilaceae is here circumscribed to include 10 genera, Acrochila, Chiastocaulon, Dinckleria, Pedinophyllopsis, Pedinophyllum, Plagiochila, Plagiochilidium, Plagiochilion, Pseudolophocolea and Xenochila. For the forthcoming world checklist of hornworts and liverworts we here summarize the current knowledge and identify the sections of Plagiochila that are currently recognized by morphological and molecular studies. Plagiochila is provisionally divided into 28 sections based on recent morphological and molecular studies. Plagiochila ecuadorica and Plagiochila sciophila subsp. ciliigera are new combinations, Plagiochila umbrosioides is a nomen novum.